Glass transitions for freeze-dried and air-dried tomato - Telis, VRN; Sobral, PJA (Elsevier B.V., 2002)
Glass transition temperatures of freeze-dried tomato conditioned at various water activities at 25 C were determined by differential scanning calorimetry (DSC). Air-dried tomato with and without osmotic pre-treatment in sucrose/NaCl solutions was also analyzed. Thermograms corresponding to the low water activity domain (0.11 less than or equal to a(w) less than or equal to 0.75) revealed the existence of two glass transitions, which were attributed to separated phases formed by sugars and water and other natural macromolecules present in the vegetable. Both transitions were plasticized by water and experimental data could be well correlated by the Gordon-Taylor equation in the low-temperature domain, and by the Kwei model in the high-temperature domain. For higher water activities, the low-temperature glass transition curve exhibited a discontinuity, with suddenly increased glass transition temperatures approaching a constant value that corresponds to the T-g of the maximally freeze-concentrated amorphous matrix. The unfreezable water content was determined through the melting enthalpy dependence on the moisture content. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: tomato; glass transition; DSC; water activity; drying